Qualidade de vida e sintomas depressivos em mulheres com diabetes mellitus gestacional - Cardoso, Nadyege Pereira (2020)
INTRODUCTION: Pregnancy is a physiological event, however, during this period the pregnant woman may develop diseases that adversely affect maternal-fetal health, such as Gestational Diabetes Mellitus (DMG), which has a high prevalence among women with hyperglycemia in pregnancy, interferes with life Quality of Life (QOL) and is related to the development of depressive symptoms OBJECTIVE: To evaluate the QoL and presence of depressive symptoms in women with GDM. METHOD: Cross-sectional, case-control, exploratory study with a quantitative approach. The sample was composed of 47 pregnant women with DMG, Test Group (GT) and 94 pregnant women classified as usual risk, Control Group (CG). Three instruments were used, one for the characterization of the sample, the other two for the assessment of QOL, the World Health Organization Quality Of Life WHOQOL- Bref and the depressive symptoms, the Edinburgh Postnatal Depression Scale (EPDS). RESULTS: Pregnant women in the TG showed lower averages than the CG in all domains of the Whoqol-bref (p <0.05). The presence of depressive symptoms during pregnancy occurred in five pregnant women (10.65%) in the TG and none in the CG. Among the sociodemographic, clinical and obstetric variables, women in the TG with a high BMI had impaired QOL in the Physical (34.07, p = 0.01), Psychological (62.38, p = 0.05), Social (64.41, p = 0.04) and in the General QOL (51.97, p = 0.00), as well as those with low educational level, presented QoL impairment in the Environment domain (46.58, p = 0.029); Those who had a family history of DM showed impairment in the Psychological (53.33, p = 0.01) and Social (45.00, p = 0.02) domains and, depending on the treatment used, in the Physical, Psychological and general QoL domains ( p <0.05). A moderate correlation was observed in the WG between the Physical domain and the Psychological domain and the general average of the Whoqol bref, between the Psychological and Social domain and between the Environment and the general average. The correlation was also strong between the Psychological domain and the general QOL, as well as between the Social and the general QOL. The other correlations were weak, that is, without clinical importance (r <0.30). In the CG, a moderate correlation was observed between the Social and Physical domains, and between Environment with Psychological and Social. All domains Physical, Social, Psychological and Environment presented a strong correlation with the general QOL. The correlation of the Whoqol-bref domains with the EPDS was negative and moderate compared to the Physical, Psychological, Social domains and the general QOL. CONCLUSIONS: The results suggest that DMG compromises QOL and predisposes to the development of depressive symptoms. There was no correlation between QoL and depressive symptoms among women with GDM, however, this correlation was identified in the group of women at habitual risk. Education level, BMI, gestational weight, family history with DM and the type of treatment were variables that interfered with QOL and the development of depressive symptoms.